The Psychology of Global Citizenship: A Review of Theory and Research - Reysen, Stephen; Katzarska-Miller, Iva (Lexington Books, 2020)
In The Psychology of Global Citizenship: A Review of Theory and Research, Stephen Reysen and Iva Katzarska-Miller provide a theoretical and empirical overview of global citizenship and related concepts. The authors highlight core components shared by a variety of disciplines and cultures and linked to pro-social values, such as the promotion of empathy, diversity, environmental sustainability, and intergroup helping. Utilizing a social psychological perspective, Reysen and Katzarska-Miller provide an integrated approach to global citizenship identification with their model of antecedents (global awareness and normative environment) and outcomes (six clusters of pro-social values).